Adapting of Mental Healthcare Facilities to the COVID-19 Challenges - Samsudeen O. Amusa (Health Economics and Management Review)
The healthcare sector is one of the largest in the US economy (generating about 18% of GDP). It is the main employer of American workers. Unfortunately, it has been one of those most affected by the COVID-19 pandemic, as certain medical services had to be suspended under strict quarantine (at least 150 hospitals in the US were forced to send employees on leave or dismiss them, primary care practices reported a 70% decrease in the number of patients). The purpose of the article is to analyse challenges in the US healthcare sector during COVID-19 and to justify ways to overcome these challenges (on the example of the Life Chance Mental Health Medical Group, a leading provider of mental health services in the US with a strong regional network, established good reputation and a wide and loyal customer base). The case of this company was chosen in this context based on the fact that, as the SWOT analysis in the article showed, during the COVID-19 pandemic, the greatest vulnerabilities of medical institutions in the mental health sector are related to the quality of basic services (face-to-face therapy sessions). That is significantly reduced if provided online. In order to operate effectively even during epidemics and pandemics, companies in this specific area should expand partnerships with telemedicine platforms, transform their product portfolio, and ensure that their doctors’ qualification profiles meet the requirements of remote therapy. The article analyses the mechanisms for overcoming pandemic challenges in mental healthcare facilities using the postulates of transformational leadership theory, change management theory, theory of constraints, and organisational culture theory.